2022
DOI: 10.1038/s42003-022-03395-9
|View full text |Cite
|
Sign up to set email alerts
|

Neocortical localization and thalamocortical modulation of neuronal hyperexcitability contribute to Fragile X Syndrome

Abstract: Fragile X Syndrome (FXS) is a monogenetic form of intellectual disability and autism in which well-established knockout (KO) animal models point to neuronal hyperexcitability and abnormal gamma-frequency physiology as a basis for key disorder features. Translating these findings into patients may identify tractable treatment targets. Using source modeling of resting-state electroencephalography data, we report findings in FXS, including 1) increases in localized gamma activity, 2) pervasive changes of theta/al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 110 publications
2
31
0
Order By: Relevance
“…Alpha activity can be viewed as a continuum, such that low alpha power is associated with continuous cortical processing, but high alpha power states can lead to inhibition of cortical circuits though alpha phase dynamics 60 . Recently, we detected a marked reduction in resting absolute and relative alpha power in males with FXS, but relatively spared in females 50, 61 . Our conclusion suggested that males with FXS have evidence of thalamocortical dysfunction which leads to slower peak frequency, reduced alpha activity, and localized increases in broadband gamma power.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Alpha activity can be viewed as a continuum, such that low alpha power is associated with continuous cortical processing, but high alpha power states can lead to inhibition of cortical circuits though alpha phase dynamics 60 . Recently, we detected a marked reduction in resting absolute and relative alpha power in males with FXS, but relatively spared in females 50, 61 . Our conclusion suggested that males with FXS have evidence of thalamocortical dysfunction which leads to slower peak frequency, reduced alpha activity, and localized increases in broadband gamma power.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, we detected a marked reduction in resting absolute and relative alpha power in males with FXS, but relatively spared in females 50,61 . Our conclusion suggested that males with FXS have evidence of thalamocortical dysfunction which leads to slower peak frequency, reduced alpha activity, and localized increases in broadband gamma power.…”
Section: Contribution Of Deep Brain Sources To Neural Synchronizationmentioning
confidence: 91%
See 1 more Smart Citation
“…FXS patients precise gamma synchrony to sensory input is impaired [18] and asynchronous background gamma activity is increased [18,25,55]. In full mutation, nonmosaic males with FXS, increased gamma power is associated with increased severity across behavioral domains (i.e., irritability, abnormal speech, hyperactivity) as well as cognitive function [55].…”
Section: Discussionmentioning
confidence: 99%
“…FXS patients precise gamma synchrony to sensory input is impaired [18] and asynchronous background gamma activity is increased [18,25,55]. In full mutation, nonmosaic males with FXS, increased gamma power is associated with increased severity across behavioral domains (i.e., irritability, abnormal speech, hyperactivity) as well as cognitive function [55]. Our finding of co-occurring RBAC-associated theta band power increase and gamma band reduction is consistent with our prior hypothesis that in FXS increased theta may be recruited to downregulate gamma activity and thus potentially suppress sensory hyperexcitability [25] thus showing a potential mechanistic signature of RBAC use in FXS.…”
Section: Discussionmentioning
confidence: 99%